Patterns of research and scientific growth on complex regional pain syndrome: bibliometric analysis of global scope: Patrones de investigación y crecimiento científico sobre el síndrome doloroso regional complejo: Análisis bibliométrico de alcance global - Moscoso-Organista, José Luis (2024)
Introduction: Complex Regional Pain Syndrome (CRPS) is a pathological entity that carries a high burden of disease and reduces disability-free life expectancy and quality of life. Previously, the research patterns and general characteristics of the scientific production on CRPS have not been evaluated or analyzed. Methods: Cross-sectional bibliometric study that used Scopus as the data source. Results: 3081 documents were selected, published between 1969 and 2024. 69% (n=2126) of the articles corresponded to original articles, followed by 13.2% (n=406); it was observed an international collaboration accounted for 11.49% and an annual scientific growth accounted for 7.63%. The most frequently used terms in CRPS research are causalgia, rehabilitation, allodynia, treatment, and inflammation. Reflex sympathetic dystrophy, causalgia, and spinal cord stimulation are the most popular topics to date. As an emerging central theme, there is increasing research on cortical reorganization. The construction of the thematic map revealed that niches of topics include depression and quality of life, as well as autoimmunity. Conclusions: This study revealed a significant increase in global research and scientific publications on CRPS, with the United States being the most prolific country and achieving the greatest impact. However, it is Dutch institutions that have made the most substantial contributions to this research field. Among the most common research patterns, it is found that causalgia, rehabilitation, allodynia, treatment, and inflammation are the most frequently used keywords, while reflex sympathetic dystrophy, causalgia, and spinal cord stimulation are the most addressed topics to date.